PENGARUH MODAL PSIKOLOGI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA DENGAN RESISTENSI PERUBAHAN SEBAGAI MODERASI (Studi Pada Biro Umum Sekretariat Daerah Provinsi Jawa Tengah) - Izyana Purbaningrum, 1342020004 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze whether there is influence psychological capital and organizational commitment influence on the performance of the resistance changes as moderation. Sampling was done by purposive sampling method the employees of the Bureau of the General Secretariat of Central Java province which amounted to 102 as a sample. Engineering test data used in this study include test validity by factor analysis, reliability testing with Cronbach alpha formula, regression analysis, and the significance test, the coefficient of determination to prove the research hypothesis and test moderation. The results showed that; psychological capital have a significant effect on performance. Organizationalcommitment significantly influence performance. Psychology capital on performance weakened by resistance changes. Organizational commitment has no significant effect on the performance moderated by the resistance change. Keywords: psychological capital, organizational commitment, performance, resistance change